The impact of immigration on the employment of natives in regional labour markets: a meta-analysis - Simonetta Longhi; Peter Nijkamp; Jacques Poot (University of Essex, Institute for Social and Economic Research (ISER), 2006)
Immigration is a phenomenon of growing significance in many countries. Increasing social tensions are leading to political pressure to limit a further influx of foreign-born persons on the grounds that the absorption capacity of host countries has been exceeded and social cohesion threatened. There is also in public discourse a common perception of immigration resulting in economic costs, particularly with respect to wages and employment opportunities of the native born. This warrants a scientific assessment, using comparative applied research, of the empirical validity of the perception of a negative impact of immigration on labour market outcomes. We apply meta-analytic techniques to 165 estimates from 9 recent studies for various OECD countries and assess whether immigration leads to job displacement among native workers. The consensus estimate of the decline in native-born employment following a 1 percent increase in the number of immigrants is a mere 0.024 percent. However, the impact is somewhat larger on female than on male employment. The negative employment effect is also greater in Europe than in the United States. Furthermore, the results are sensitive to the choice of the study design. For example, failure to control for endogeneity of immigration itself leads to an underestimate of its employment impact.
Keywords: 330